PENGEMBANGAN MODEL TUTORING POLICY UNTUK MEMAKSIMALKAN PREFERENSI MAHASISWA MENGGUNAKAN PENDEKATAN TEORI KEPUTUSAN - , Mithafirsty Annisa C; , Nur Aini Masruroh, ST. MSc., Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Teaching method is an important issue in terms of education because it can influence the successfulness of a learning process and an education quality. However, current teaching methods are often not optimal. It is affected by uncertain factors, such as student ability, resource, environment and culture. Based on those factors, several teaching methods are provide alternatives for the current method. Every method has different effectivity level given different circumstances. Yet, the complexity of a system, the uncertainty and the objective are factors that cause the decision hard to make. Therefore, this research aims to construct the most suitable tutoring policy model to maximize the studentâs preference in the courses containing mathematic elements above 50% and containing mathematic elements below 50%. The subjects of the research is post-graduate students of the Industrial Engineering Program of Universitas Gadjah Mada.The model is developed by using Influence Diagram (ID) considering uncertain factors, such as student ability, studentâs effort, preparation, learning style, level of intellectual, and learning approach simultaneously. The data is collected by distributing four types of questionnaire, which are Analytical Hierarchy Process (AHP) questionnaire, Index of Learning Style (ILS) quissionaire, Learning Approach questionnaire and Intellectual Level questionnaire. This research contains four teaching method choices, i. e. general discussion method, lecture method, experimental method and problem solving method. The result shows that the most prefered teaching method for the courses containing mathematic elements above 50% is general discussion whereas for the courses containing mathematic elements below 50% is problem solving. Eventually, the final decision model can be considered as valid because the validity test and the case study show consistent results.